Rubber dam as a barrier membrane in the treatment of periodontal osseous defect - Girish Nagarale; Srinath Thakur; S Ravindra (Indian Journal of Dental Research, 2012)
Background: Barrier membrane helps in periodontal regeneration by preventing the migration of epithelial cells and cells from the gingival connective tissue onto the root surface. Different types of membranes have been used to regenerate periodontal tissues. There are very few documented reports where rubber dam has been used as a barrier membrane for regeneration of periodontal defects. Case Description: A female patient aged 20 years with localized aggressive periodontal disease participated in this clinical report. Infrabony defect in the lower anterior region was selected for surgical treatment. Rubber dam was trimmed to cover the defect. Orthodontic treatment was done for the realignment of malpositioned teeth 1 year after the surgery and patient was followed up for a period of 3 years after surgery. Results: Rubber barrier membrane did not result in any untoward side effects. Patient did not show any sign of inflammation or recurrence of probing depth at 3-year follow-up period. Clinical Implications: Rubber dam as barrier membrane yields good results.